Prospects for H-mode inhibition in negative triangularity tokamak reactor plasmas. (1st September 2022) - Nelson, A.O.; Paz-Soldan, C.; Saarelma, S.
Abstract: Instability to high toroidal mode number ( n ) ballooning modes has been proposed as the primary gradient-limiting mechanism for tokamak equilibria with negative triangularity (NT) ( δ ) shaping, preventing access to strong H-mode regimes when δ is sufficiently negative. To understand how this mechanism extrapolates to reactor conditions, we model the infinite- n ballooning stability as a function of internal profiles and equilibrium shape using a combination of the CHEASE and BALOO codes. While the critical δ required for avoiding 2nd stability to high- n modes is observed to depend in a complicated way on various shaping parameters, including the equilibrium inverse aspect ratio, elongation and squareness, equilibria with NT are robustly prohibited from accessing the 2nd stability region, offering the prediction that NT reactors should maintain L-mode-like operation. In order to access high- n  2nd stability, the local shear over the entire bad curvature region must be sufficiently negative to overcome curvature destabilization on the low field side. Scalings of the ballooning-limited pedestal height are provided as a function of plasma parameters to aid future scenario design.